2015
DOI: 10.1063/1.4931929
|View full text |Cite
|
Sign up to set email alerts
|

A semi-annular shock tube for studying cylindrically converging Richtmyer-Meshkov instability

Abstract: A novel semi-annular shock tube is realized by combining the advantageous features of two types of existing facilities for generating cylindrically converging shock waves. A high-speed schlieren photography is used to acquire the variation of shock positions versus the time and the evolution of a single-mode gaseous interface subjected to the cylindrical shock. The first experimental results indicate that the semi-annular configuration brings great convenience for interface formation and flow visualization, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…As shown in figure 4, there exists only a minor difference between the linear and nonlinear predictions even at very late stages, which indicates a very weak nonlinearity for the divergent RMI. This finding is completely different from that of convergent RMI where nonlinearity is found to be strong and behaves evidently (Wang et al 2015;Luo et al 2019). The growth of the third harmonic together with its feedback to the primary mode, predicted by the nonlinear model of Wang et al (2015), is also shown in figure 4 (the growth of the second harmonic produces no influence on the whole perturbation growth and is not given).…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…As shown in figure 4, there exists only a minor difference between the linear and nonlinear predictions even at very late stages, which indicates a very weak nonlinearity for the divergent RMI. This finding is completely different from that of convergent RMI where nonlinearity is found to be strong and behaves evidently (Wang et al 2015;Luo et al 2019). The growth of the third harmonic together with its feedback to the primary mode, predicted by the nonlinear model of Wang et al (2015), is also shown in figure 4 (the growth of the second harmonic produces no influence on the whole perturbation growth and is not given).…”
Section: Resultsmentioning
confidence: 70%
“…The growth of the third harmonic together with its feedback to the primary mode, predicted by the nonlinear model of Wang et al (2015), is also shown in figure 4 (the growth of the second harmonic produces no influence on the whole perturbation growth and is not given). It is found that at early stages the growth of the third harmonic in divergent geometry is much smaller than that in a planar or convergent geometry (Luo et al 2019), which provides a further demonstration of weak nonlinearity. Although nonlinearity increases at late stages, the positive growth of the third harmonic approximately counteracts its negative feedback to the basic mode, which suggests a negligible influence of nonlinearity on the growth of overall perturbation amplitude.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The converging RM instability has rarely been studied in a shock tube circumstance mainly due to the difficulty of generating a stable converging shock in laboratory conditions. There are only few works on the cylindrically converging shock (Perry & Kantrowitz 1951;Takayama, Kleine & Grönig 1987;Dimotakis & Samtaney 2006;Zhai et al 2010;Luo et al 2015) and, consequently, shock tube experiments on the converging RM instability are scarce (Hosseini & Takayama 2005;Si, Zhai & Luo 2014;Biamino et al 2015;Si et al 2015). Recently, two quantitative shock tube experiments were, respectively, reported in a semi-annular converging shock tube (Ding et al 2017) and a coaxial converging shock tube (Lei et al 2017), in which a reduction of growth rate was found and was ascribed to the RT stabilization effect caused by the interface deceleration motion existing in the converging circumstance.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the limited apex angle of the converging geometry, the wedge boundaries often have significant influence on the evolution of the interface deformation and the shock propagation. To overcome these shortcomings, a semi-annular shock tube that combines the advantageous features of the above-mentioned two types of facilities was realized by Luo et al 123 The design of this shock tube followed the similar principle of an annular configuration, but the annular channel and the test section were cut into half and assembled in a self-strutted manner. In this way, the semi-annular configuration brings great convenience for interface formation and flow visualization, which are considered to be the two crucial ingredients in RM instability experiments.…”
Section: Interaction Of a Converging Shock Wave With A Gaseous Interfacementioning
confidence: 99%